Muslims and Buddhist interaction in Pasir Mas, Kelantan - Mohd Amin, Wan Mohd Adam; Mohd Rashid, Zuriati (Malaysian Association of Modern Languages, 2010)
Although Malaysia is a predominantly Muslim country, other religions such as Buddhism, Hinduism, Christianity, Sikhism, Taoism, and other traditional belief systems are also practiced. The objective of this study is to explore the relationship or religious interaction between Muslims and Buddhists in one of the east coast states in Malaysia, Kelantan. A small town, Pasir Mas is chosen as it consists of two major religions, Islam and Buddhism, forming two religious communities living side by side in a traditional village namely Kg. Tendong. It is an ethno-religious study of Malay Muslims and Chinese as well as Siamese Buddhists in terms of their religious interaction in the said location. The study in Pasir Mas could be perceived as a subset study over the dominant set of ethnic groups in Malaysia. In order to measure the quality of interaction, some indicators have been prepared to be applied on a total of one hundred and forty (140) respondents that were drawn from Muslims and Buddhists. The sample size together with the above-mentioned indicators showed that the quality of interaction is encouraging in the sense that the universal values of the two religions, namely Islam and Buddhism that bind people together. On the other hand, the discouraging factor of interaction among the residents of Pasir Mas was that trivial issues of religious differences. Therefore, the significance of the study lies mainly in showing the level of interaction between Muslims and Buddhists in Pasir Mas. This result is essential to the policy makers to develop a better pattern of inter-racial interaction in a remote area of Peninsular Malaysia. The study finally discusses the need for broader and more comprehensive research in this area.